Modeling and analysis of flutter-based thin-film cantilever microgenerator - Abdul Hakim, Javid; Raed, Kafafy; Erwin, Sulaeman; Sany, Ihsan; Mahmoud Idres, Moumen Mohammed (Asian Research Publishing Network (ARPN), 2015)
This paper presents a model for design and analysis of flutter-based microgenerators and a new concept for wind energy harvesting using thin-film cantilever with coils embedded on the sides of the cantilever. The analytical model predicts the flow-induced response of the thin-film cantilever at various parameters as well as the frequency of flutter at a wind speed which is crucial for designing a flutter based microgenerator. A complete analytical model unites various physics involved, flow induced forces on the cantilever, mechanical vibrations, electromagnetic coupling, and electric power output. The flutter frequency predicted by the analytical model is verified against finite element analysis using NASTRAN. The effect of span, width of the cantilever, length of coil on the cantilever and load resistance is investigated on the performance of the harvester. The results predicted by the analytical model agree reasonably well with the finite element analysis results paving way of using such an analytical model to design and optimize a fluttering wind energy harvester.